Performance of Malaysian Insurance Companies Using Data Envelopment Analysis - Ng Jia Bao; Rohaizan Ramlan; Fazeeda Mohamad; Azlina Md Yassin (Institute of Advanced Engineering and Science, 2018)
The purpose of this study is to evaluate the performance of the local insurance in Malaysia for the period 2014-2015. The major challenge in the insurance industry is increasing competition in this market. Besides that, problematic in performance measurement to evaluate performance is another challenge in insurance industry. 24 local insurance companies involved in this study using quantitative method of Data Envelopment Analysis (DEA) output-orientation CCR model. This study utilizes three inputs and three outputs; operating expenses, equity capital and commission as well as net premium, net investment income, and net incurred claim. The secondary data sources were derived from official data of local insurance companies’ annual report respectively. The DEA-Solver-LV version 8 tools were used to analyze the data that have been collected to evaluate the performance of local insurance company. This DEA model allows integration of the performance for the insurance companies and provides management overall performance evaluation. The results showed that there are 8 efficient companies in 2014 and 9 efficient companies in 2015. The average efficiency score in 2014 was increased from 78.9% to 79.1% in 2015. The findings from this study will benefit the insurance associations in Malaysia, management of insurances companies and policy makers.